Approaching the Compressive Modulus of Articular Cartilage With a Decellularized Cartilage-Based Hydrogel - Beck, Emily C. (Acta Biomater, 2016)
ECM-based materials are appealing for tissue engineering strategies because they may promote stem cell recruitment, cell infiltration, and cell differentiation without the need to supplement with additional biological factors. Cartilage ECM has recently shown potential to be chondroinductive, particularly in a hydrogel-based system, which may be revolutionary in orthopedic medicine. However, hydrogels composed of natural materials are often mechanically inferior to synthetic materials, which is a major limitation for load-bearing tissue applications. The objective was therefore to create an unprecedented hydrogel derived entirely from native cartilage ECM that was both mechanically more similar to native cartilage tissue and capable of inducing chondrogenesis. Porcine cartilage was decellularized, solubilized, and then methacrylated and UV photocrosslinked to create methacrylated solubilized decellularized cartilage (MeSDCC) gels. Methacrylated gelatin (GelMA) was employed as a control for both biomechanics and bioactivity. Rat bone marrow-derived mesenchymal stem cells were encapsulated in these networks, which were cultured in vitro for 6 weeks, where chondrogenic gene expression, the compressive modulus, swelling, and histology were analyzed. One day after crosslinking, the elastic compressive modulus of the 20% MeSDCC gels was 1070 ± 150 kPa. Most notably, the stress strain profile of the 20% MeSDCC gels fell within the 95% confidence interval range of native porcine cartilage. Additionally, MeSDCC gels significantly upregulated chondrogenic genes compared to GelMA as early as day 1 and supported extensive matrix synthesis as observed histologically. Given that these gels approached the mechanics of native cartilage tissue, supported matrix synthesis, and induced chondrogenic gene expression, MeSDCC hydrogels may be promising materials for cartilage tissue engineering applications. Future efforts will focus on improving fracture mechanics as well to benefit overall biomechanical performance.